Documenting the course of loss of control over eating prior to, during and after pregnancy among women with pre‐pregnancy overweight and obesity. Issue 4 (23rd December 2020) - Donofry, Shannon D.; Emery, Rebecca L.; Kolko Conlon, Rachel P.; Germeroth, Lisa J.; Wang, Bang; Cheng, Yu; Levine, Michele D.
Abstract: Objective: Loss of control over eating (LOC) is common among women, particularly those with overweight and obesity (OV/OB), and predicts weight gain. Given the importance of understanding weight and eating behaviors during pregnancy, we sought to characterize LOC across pregnancy and the postpartum period among women with pre‐pregnancy OV/OB. Methods: Pregnant women ( N = 257; 28.44 ± 5.48 years old) with self‐reported OV/OB prior to pregnancy were interviewed using a pregnancy‐adapted version of the Eating Disorder Examination (EDE‐PV). Pre‐pregnancy LOC was retrospectively assessed during the first trimester and then prospectively assessed monthly throughout pregnancy and postpartum over the course of seven assessments. Results: Rates of LOC were significantly higher during pregnancy compared to prior to ( χ 1 2 =44.845, p < .01) and after ( χ 1 2 =36.379, p < .01) pregnancy, with 37% ( n = 95) of women reporting ≥1 LOC episode during pregnancy. LOC during pregnancy was associated with higher likelihood of LOC postpartum. Higher age (OR = 1.084, p = .04) and identifying as a minority (OR = 0.344, p = .02) was associated with greater likelihood of experiencing LOC during pregnancy only. Discussion: LOC during pregnancy is common among women with pre‐pregnancy OV/OB, suggesting that screening and intervention for LOC during pregnancy may be warranted. Future research is necessary to examine the relationship between LOC during pregnancy and maternal and infant health outcomes.